Theatre of the Absurd and Rajeshwar Prasad’s Art of Characterisation in His Absurd Plays - Ramsurat (International Journal of Language and Literary Studies, 2026)
The objective of this study is to explore the Theatre of the Absurd as seen through a comparative lens. More specifically, through an analysis of Rajeshwar?Prasad’s seven plays of Theatre of the Absurd, how he characterizes characters using unique characterisation techniques. Through an examination of Prasad’s use of fragmented dialogue, symbolic staging, and paradoxical characters, when mapped onto some modern playwrights and the canonical models established by Beckett, Ionesco, and their successors, it reveals two simultaneous themes embodied by the characters of Rajeshwar?Prasad: one that displays a faith-filled, hopeful attitude, and the other a stark nihilistic attitude. This duality serves as a form of rebellion against strict narrative conventions, thereby incorporating the joylessness that is natural to humans and our desire for meaning. As illustrated in this analysis, Prasad’s "absurd formula" of (aclp2t) + (afi2lms) + (tc) is very effective through the very characters that the playwright has created and revealed. Gradually, Prasad unveils life’s ’absurdity’.